OP0046 Tofacitinib, an Oral Janus Kinase Inhibitor, in a Rheumatoid Arthritis Open-Label Extension Study Following Adalimumab Therapy in a Phase 3 Randomised Clinical Trial. (23rd January 2014) - Genovese, M.; van Vollenhoven, R.; Wilkinson, B.; Wang, L.; Zwillich, S.; Gruben, D.; Benda, B.; Jones, T.; Bradley, J.
Abstract : Background: Tofacitinib is a novel oral Janus kinase inhibitor for the treatment of rheumatoid arthritis (RA). Objectives: Describe efficacy and safety for adalimumab (ADA) patients (pts) transitioning to tofacitinib open label extension (OLE) without washout. Methods: In the Phase 3 randomised controlled trial (RCT, NCT00853385 ) ORAL Standard, pts on background MTX received tofacitinib 5 mg BID, tofacitinib 10 mg BID, ADA 40 mg sc injections (Q2 Wk), placebo (PBO) to tofacitinib 5 mg BID, or PBO to tofacitinib 10 mg BID (4:4:4:1:1). Primary results were reported. 1 Eligible pts from the RCT were permitted to enrol in an OLE receiving tofacitinib 10 mg BID without washout (last RCT ADA dose to first OLE tofacitinib dose ≤1 Wk). In this post-hoc analysis, results are described for ADA pts 4.5 months (Mo) before and at end of the RCT, and 4.5 Mo after transition to tofacitinib in OLE. Data for tofacitinib 10 mg BID during RCT and OLE are shown at the same time points. Results: 145 of 204 pts randomised to ADA were eligible and enrolled in OLE; 125 started tofacitinib without washout. There were 8 (6.4%) discontinuations during the first 4.5 Mo of OLE (3 drug-related AE, 1 unrelated AE, 1 pregnancy, 1 death, 2 other reasons). 148 of 201 pts randomised to tofacitinib 10 mg BID were eligible and enrolled in OLE; 124 took their first dose of tofacitinib in the OLE ≤1 Wk after their last dose of tofacitinib in the RCT. There were 9 discontinuations in the first 4.5 Mo of OLE (1 drug-related AE, 2 unrelated AE, 6 other reasons). ACR20 response rate in ADA to tofacitinib pts (N= 124) was 74.2% at 4.5 Mo before end of RCT, 76.6% at end of RCT, and 90.5% at 4.5 Mo after transition to tofacitinib. ACR50 response rates (44.4%, 50.8%, 65.5%) and ACR70 response rates (16.1%, 21.0%, 36.2%) at the same time points showed a similar pattern. Mean change from baseline in HAQ-DI was -0.55, -0.60, and -0.70 at the same time points. Results in tofacitinib to tofacitinib pts were similar at the same time points and showed a similar pattern of increases from RCT to OLE. Image/graph: Conclusions: Changing directly from ADA in RCT to tofacitinib in OLE resulted in sustained clinical response, with numerical improvements in ACR 20, 50, and 70 response rates and mean change in HAQ-DI from baseline. Safety-related events appeared to increase post-transition from ADA to tofacitinib; however, similar increases were seen in pts treated with tofacitinib in the RCT after they transitioned to OLE tofacitinib. The increase in safety-related events in both groups suggests that the increase was not simply the result of overlapping immunomodulatory effects of ADA and tofacitinib. References: R.F. van Vollenhoven et al. N Engl J Med 2012; 367: 508-519. Disclosure of Interest: M. Genovese Grant/research support from: Pfizer Inc, Consultant for: Pfizer Inc, R. van Vollenhoven Grant/research support from: AbbVie, BMS, GSK, MSD, Pfizer Inc, Roche, UCB, Consultant for: AbbVie, BMS, GSK, MSD, Pfizer Inc, Roche, UCB, B. Wilkinson Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, L. Wang Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, S. Zwillich Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, D. Gruben Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, B. Benda Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, T. Jones Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, J. Bradley Shareholder of: Pfizer Inc, Employee of: Pfizer Inc